Cardiorespiratory fitness, but not central obesity or C-reactive protein, is related to liver function in obese children - Martins, Clarice; Freitas Jr., Ismael [UNESP]; Pizarro, Andréia; Aires, Luísa; Silva, Gustavo; Santos, Maria Paula; Mota, Jorge (My University, 2013)
Nonalcoholic fatty liver disease (NAFLD) is one of the most frequent complications associated with excess adiposity. Its pathogenesis is complex and there are multiple factors that may contribute to it. AIM: To analyze whether cardiorespiratory ftness (CRF), waist circumference (WC), and C-reactive protein (CRP) are associated with alanine aminotransferase (ALT) in children with obesity. METHODS: 79 overweight/obese children of both genders, 11-13 year-olds, with abnormal serum ALT from Porto public schools comprised the sample. Measurements included CRF (20-m Shuttle Run Test), WC (NHANES protocol), CRP and ALT (Cholestech LDX analyzer). Logistic regression adjusted for gender, maturation, and weight with ALT levels as dependent variable (risk vs. non risk), and WC (risk vs. non risk), CRP (risk vs. non risk), and CRF (fit vs. unfit) as independent variables. Level of significance was set at 95%. RESULTS: Logistic regression showed that obese fit children were less likely to have abnormal ALT values (OR=.031) CONCLUSION: In obese children, higher cardiovascular fitness appears to reduce the chance of decreased liver function. © 2013 Human Kinetics, Inc.
Keywords: alanine aminotransferase; C reactive protein; adolescent; blood; cardiovascular function; child; exercise test; female; fitness; human; liver; male; metabolism; obesity; pathophysiology; physiology; statistical model; waist circumference; Adolescent; Alanine Transaminase; C-Reactive Protein; Cardiovascular Physiological Phenomena; Child; Exercise Test; Female; Humans; Liver; Logistic Models; Male; Obesity; Physical Fitness; Waist Circumference